L’agglomération de Bliesbruck (Moselle) durant l’Antiquité tardive : entre ruptures et continuités - Sonia Antonelli; Jean-Paul Petit (Gallia)
The contribution analyses the transformation process of Bliesbruck – a small town in the civitas of the Mediomatrici – in Late Antiquity. Despite the vicissitudes in the years 260-280 AD, there is no break in the occupation. The urban structure was preserved until after the middle of the 4th c. AD, but the public centre lost part of its function and one of the districts is no longer occupied. Marked transformations occurred during the third quarter of the 4th c. The occupation is restricted to the central part dominated by the public thermal complex. Some buildings are abandoned, others transformed by timber post constructions or using materials of re-use. The occupation – which continued until the middle of the 5th c. – is characterised by a strong artisanal activity, such as copper alloys-working from recovered metal, the important diffusion of Argonne and Eifel ceramics and the circulation of numerous coins, including a remarkable proportion of the extreme end of the 4th and 5th c. The discovery of finery objects and militaria, some of which have “germanic” or “oriental” characters, also raises the question of a military presence and shows that the town is integrated into long-distance commercial networks and inserted into the german-danubian cultural world of Late Antiquity.